1982
DOI: 10.1002/ijc.2910300504
|View full text |Cite
|
Sign up to set email alerts
|

Application of the micronucleus test to exfoliated cells of high cancer risk groups: Tobacco chewers

Abstract: Powdered tobacco (Khaini tobacco) with the addition of lime is commonly used by the residents of Bihar, India. The tobacco/lime mixture is usually placed on the inner side of the lower lip within the gingivolabial groove. About 42% of the users keep it at the front, the rest move the tobacco towards the left or right side within the oral cavity. Carcinomas (so-called "Khaini cancers") develop mainly at the site where the tobacco is in close contact with the mucosa. Scrapings of the mucosa were taken at sites w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
9

Year Published

1983
1983
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(70 citation statements)
references
References 21 publications
1
60
0
9
Order By: Relevance
“…This also affects the lower lip more commonly than the upper one. About 42% of the users keep it in front (Stich et al, 1982), thus predisposing to development of cancer lower lip as being in close proximity. Poor dental hygiene may play a role in the etiology of the lip cancer as sharp jagged teeth, poorly fitting dentures and chronically infected gingiva may cause persistent irritation of lips.…”
Section: Cancer Of Lipmentioning
confidence: 99%
See 1 more Smart Citation
“…This also affects the lower lip more commonly than the upper one. About 42% of the users keep it in front (Stich et al, 1982), thus predisposing to development of cancer lower lip as being in close proximity. Poor dental hygiene may play a role in the etiology of the lip cancer as sharp jagged teeth, poorly fitting dentures and chronically infected gingiva may cause persistent irritation of lips.…”
Section: Cancer Of Lipmentioning
confidence: 99%
“…Amongst tobacco chewers about 58% of the users (Stich et al, 1982), move the tobacco towards left or right side within the oral cavity whereby carcinogens percolate admixed with saliva to cause irritation of the adjoining mucosa and tongue. It may be possible to have more predisposition of lateral boarder of tongue as compared to tip since it is relatively less mobile and with larger surface area, and hence more exposed to the carcinogen mixed saliva.…”
Section: Cancer Tonguementioning
confidence: 99%
“…Use of alcohol also potentiated tobacco-related carcinogenesis which was an independent risk factor. [25][26] Though there are initiatives taken up by the Government to impart awareness on the harmful effects, tobacco and alcohol related cancers are on the rise in the country. Therefore, a more stringent protocol has to be adopted to ban or control the supply and access to tobacco and alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy (25,26) Radiotherapy ( In the study population, 41 different types of cancers were observed. HNCs included mostly the squamous cell carcinomas of the post-cricoid, tonsils, base of tongue, nasopharynx, larynx, pyriform fossa, posterior pharyngeal wall, floor of mouth, tongue, gingivobuccal sulcus, neck, maxilla, hypopharynx, epiglottis, supraglottis, thyroid and retromolartrigone.…”
Section: Treatment (M W)mentioning
confidence: 99%
“…Este análisis tiene las siguientes ventajas: las células no necesitan ser cultivadas, los micronúcleos pueden reflejar eventos genotóxicos que han ocurrido en las células de división basal en las últimas tres semanas, la técnica es rápida, simple y las muestras son fáciles de obtener (Tolbert et al 1991). En algunos estudios se han informado frecuencias más elevadas de micronúcleos en individuos expuestos al consumo de alcohol y tabaco, encontrándose una relación directamente proporcional entre el número de micronúcleos y el tiempo de exposición (Livingston et al 1990, Stich et al 1982, Tolbert et al 1991. Los resultados de otros estudios son variables, dependiendo del tipo de tejido, así como de las condiciones de la investigación en general (Pastor et al 2001, Pastor et al 2002.…”
unclassified